Probing cell identity hierarchies by fate titration and collision during direct reprogramming. Issue 9 (15th September 2022) - Hersbach, Bob A; Fischer, David S; Masserdotti, Giacomo; Deeksha,; Mojžišová, Karolina; Waltzhöni, Thomas; Rodriguez‐Terrones, Diego; Heinig, Matthias; Theis, Fabian J; Götz, Magdalena; Stricker, Stefan H
Abstract: Despite the therapeutic promise of direct reprogramming, basic principles concerning fate erasure and the mechanisms to resolve cell identity conflicts remain unclear. To tackle these fundamental questions, we established a single‐cell protocol for the simultaneous analysis of multiple cell fate conversion events based on combinatorial and traceable reprogramming factor expression: Collide‐seq. Collide‐seq revealed the lack of a common mechanism through which fibroblast‐specific gene expression loss is initiated. Moreover, we found that the transcriptome of converting cells abruptly changes when a critical level of each reprogramming factor is attained, with higher or lower levels not contributing to major changes. By simultaneously inducing multiple competing reprogramming factors, we also found a deterministic system, in which titration of fates against each other yields dominant or colliding fates. By investigating one collision in detail, we show that reprogramming factors can disturb cell identity programs independent of their ability to bind their target genes. Taken together, Collide‐seq has shed light on several fundamental principles of fate conversion that may aid in improving current reprogramming paradigms. Synopsis: Collide‐seq, a single‐cell protocol for analysing how different reprogramming transcription factors achieve conversion and how cells resolve cell identity conflicts, reveals several fundamental principles of fate conversion: The ability to erase starter cell identity is a common feature of most reprogramming factors, though their mechanisms for fate erasure differ. Reprogramming factor levels and target gene expression show a binary relationship, i.e., a functional threshold for the induction and repression of target genes. Cell identity conflicts are resolved through either factor dominance or generation of a novel transcriptomic status (a collision state) resulting in clear phenotypic consequences. Abstract : Collide‐seq, a single‐cell protocol for analysing how different reprogramming transcription factors achieve conversion and how cells resolve cell identity conflicts, reveals several fundamental principles of fate conversion.